Reforming Belgium's Federalism: Comparing the Views of MPs and Voters. Issue 3 (2nd December 2015) - Reuchamps, Min; Sinardet, Dave; Dodeigne, Jérémy; Caluwaerts, Didier
Abstract : Consociational theory posits that political elites in divided societies will show a stronger 'spirit of accommodation' than the groups they represent, and that this prudent leadership on behalf of the elites explains why divided societies hold together. Belgium has long been considered to be one of the best examples of such a consociational democracy. Yet in this country the spirit of accommodation of prudent leaders was questioned and discussed publicly during the 2010–11 political gridlock. The question is therefore whether Belgian political elites are indeed less radical and hold less extreme views than voters, as suggested by consociational theory. To explore this question, this article relies on survey data gathered during the historically long government negotiations of 2010–11 between members of all six Belgian assemblies. This original data set on MPs is compared with data on voters gathered in 2009 and 2014 in order to contrast their views on the reform of Belgium's federalism. The results show that voters are less radical than MPs on this question, but the data also reveal that MPs are strongly divided within communities and also within party. Neither communities nor parties are monolithic blocks.